Three TAS2R Bitter Taste Receptors Mediate the Psychophysical Responses to Bitter Compounds of Hops (Humulus lupulus L.) and Beer - Intelmann, Daniel; Batram, Claudia; Kuhn, Christina; Haseleu, Gesa; Meyerhof, Wolfgang; Hofmann, Thomas (Chemosensory perception, 2009)
In order to study the role of different haplotypes of taste receptor genes in food choice, it is necessary to first identify the cognate hTAS2R bitter taste receptors for the key bitter compounds in food products of our daily diet. In order to identify the candidate receptors mediating the bitter taste of hop-containing beverages such as beer, we transiently transfected plasmids encoding the 25 human TAS2Rs into human embryonic kidney 293T cells, stably expressing the chimeric G-protein G16gust44. Thereby, we coupled the activation of hTAS2R receptors to the release of Ca 2+ from intracellular stores. The transfected cells were loaded with a calcium-sensitive fluorescence dye and challenged by 15 hop-derived compounds, including α-acids, β-acids, trans / cis -iso-α-acids, isoxanthohumol, xanthohumol, and 8-prenylnaringenin. Depending on their chemical structure, all these compounds activated various combinations of the three bitter taste receptors hTAS2R1, hTAS2R14, and hTAS2R40 with distinct threshold concentrations and EC 50 values. Notably, this is the first time that an agonist for hTAS2R40 is reported. The threshold concentrations and EC 50 values obtained from the taste receptor assays were much lower than those determined by human psychophysical experiments, even though the rank order of potency for the various compounds was similar in both experiments. Thus, the subjects perceived the bitterness of the investigated compounds at higher concentrations than those predicted by the results of the in vitro experiments. These differences were shown to be due, at least in part, to interactions of the bitter substances with the oral mucosa.